Platform and data co-operatives amidst European pandemic citizenship - Calzada, I (MDPI, 2020)
EXECUTIVE SUMMARY In Europe, many citizens will likely be unemployed in the course of COVID-19. Yet the COVID-19 pandemic has shown that platform work can offer opportunities-alongside also exposing citizens to pervasive multifaceted vulnerabilities and precarious labour conditions-to continue working and earning even during times of crisis. But how can job quality be ensured for all platform workers while also creating further democratic socioeconomic platformised alternatives to revert the algorithmic and data-opolitic extractivist business-as-usual hegemonic paradigm? This chapter responds to whether it is possible to alter the existing data governance extractivist conditions for incentivising the emergence of platform and data cooperatives to further democratise and thus protect pandemic European citizens' labour and digital rights. To cite this executive summary: Calzada, I. (2020). Platform and Data Co-operatives Amidst the European Post-COVID-19 Citizenship, In Craglia, M. (ed) DigiTranScope: A Project on the Governance of/with the Digital Transformation.